Reward and Performance: Why Social and Extrinsic Rewards Fail to Improve Job Performance? - Keumala Hayati; Sinta Dewi Artha Rini (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to examine the effect of Total Reward on employee performance by integrating intrinsic, extrinsic, and social reward components within Herzberg’s Two-Factor Theory framework. The motivation for this research comes from the gap in existing literature, which often emphasizes partial reward systems, while the holistic Total Reward perspective remains underexplored, particularly in the context of employee motivation and performance in Indonesia’s banking sector. Research Methodology: The study applied a survey method by distributing structured questionnaires to bank employees in Lampung Province, Indonesia. A simple random sampling technique was employed to ensure representativeness. Data were analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS) with SmartPLS, focusing on the second-order construct of Total Reward to test the effect of intrinsic, extrinsic, and social dimensions on employee performance. Results: The findings indicate that intrinsic rewards, such as recognition, responsibility, and personal growth opportunities, significantly improve employee performance. However, extrinsic rewards (salary, benefits, working conditions) and social rewards (relationships with colleagues and supervisors) did not show a significant influence. Conclusions: The study concludes that enhancing intrinsic rewards is a key driver for boosting employee performance in the banking sector. While extrinsic and social rewards remain necessary, they are insufficient without meaningful intrinsic motivators. Limitations: This study is limited to one province and a specific industry, reducing its generalizability. Contribution: The research contributes to HR management by demonstrating the strategic value of focusing on intrinsic rewards to foster sustainable performance improvements.